2008
DOI: 10.1007/s11249-008-9352-z
|View full text |Cite
|
Sign up to set email alerts
|

Dry Reciprocating Sliding Friction and Wear Response of WC–Ni Cemented Carbides

Abstract: A number of WC-Ni based cemented carbide grades with distinctive binder contents were tested with the goal to evaluate their dry reciprocating sliding friction and wear behaviour against WC-6 wt.%Co cemented carbide using a Plint TE77 tribometer and distinctive normal contact loads. The generated wear tracks were analysed by scanning electron microscopy and quantified volumetrically using surface scanning topography. The experimental results revealed one WC-Ni grade with superior wear performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The wear track analysis revealed that the wear process of the WC-Co cemented carbides obtained by CS is controlled by abrasion, grain fracture, binder removal, adhesion, grain pull-out and tribofilm formation. [31,35,36]. The WC phase undergoes fracture, which is attributed to the local contact load, exceeding the critical fracture limit of the WC phase [35,37].…”
Section: Wear Surface Analysismentioning
confidence: 99%
“…The wear track analysis revealed that the wear process of the WC-Co cemented carbides obtained by CS is controlled by abrasion, grain fracture, binder removal, adhesion, grain pull-out and tribofilm formation. [31,35,36]. The WC phase undergoes fracture, which is attributed to the local contact load, exceeding the critical fracture limit of the WC phase [35,37].…”
Section: Wear Surface Analysismentioning
confidence: 99%
“…Cemented carbides based on WC and a ductile metal matrix (Co, Ni and/or Fe) are used in a wide range oftribological applications such as cutting, mining, metal forming, drilling and turning [1], because of their good combinations of mechanical properties such as hardness, toughness, wear resistance and strength [1,2]. These properties depend mainly on the WC grain size, type and amount of binder [3], and thus to improve on the operation life of these cemented carbides, successful manipulation of these factors is required.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness and abrasion wear resistance of WC cemented carbides produced by powder metallurgy increase with decreased WC grain size from the micron to the nanometric scale, and Co binder strengthening from increased W dissolution [1,4]. Additionally, reduced hardness with increased binder content is less in cemented carbides with finer WC grains than with micron-sized WC [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations